The web and the 50-plus - Stroud, Dick (Henry Stewart Talks, 2009)
Age and internet use, Web 2.0 architecture, Physiological ageing matters, Web 2.0 applications, Age distribution of users, Enabling technologies, Importance to marketers, The future